The Implementation of The Auto Gate System as A Facilitator of The Flow of Goods At Container Terminal (A Study At Operating Terminal 3 Ocean Going, Tanjung Priok Port). (July 2020) - Pramesti, S; Safitri, S M I; Sirait, D P; Wibisono, G; Simarmata, Juliater
Abstract: The heavy traffic of goods in the port, infrastructure and technology are needed as a support in the activity of goods traffic in the port. Terminal 3 Ocean Going IPC TPK has just implemented an auto gate as a goods flow accelerator at the port. This study aims to knowing the implementation of the auto gate system at Terminal 3 Ocean Going IPC TPK in facilitating the flow of goods and knowing the obstacles in the application of the auto gate system. The method used is qualitative descriptive by interview, observation and field research. Expected results with the existence of an auto gate system can increase the effectiveness and efficiency of services in goods traffic activities and can make it easier to control the flow of goods movements. The implementation of the auto gate system at Terminal 3 ocean going is considered good and provides many benefits, but IPC TPK has just been in a development test so that evaluation is still underway to go to the production test stage.